(untitled) (Journal of Asian Development Studies, 2025)
The relationship between macroeconomic factors and Foreign Direct Investment (FDI) in South Asian countries is investigated. This study also examines interest rates, exchange rates, oil prices, inflation, and GDP levels. The survey spanned the period from 2000 to 2020, encompassing major economic crises, including the current COVID-19 pandemic. Purposive sampling was used, and information was gathered from reputable sources, including the central banks of Pakistan. The regression model used in the study yields some interesting results. In Bangladesh, interest rates are directly proportional to inflation and GDP. They have a considerable impact on FDI (Foreign Direct Investment), while corruption is an important mediator that affects the relationship between them. FDI in India depends on many variables. Inflation rates, exchange rates, and oil prices, as well as GDP, are the most important of these; relatively few regard corruption as a serious obstacle to foreign investment. But political stability becomes an important intermediary factor. Likewise, in Pakistan, inflation rates and exchange rates will increase or decrease FDI; oil prices have a rapid impact, whereas GDP has a decelerated effect. With corruption marked as insignificant, it’s political stability that plays a significant mediating role. The study underlines the significance of government action in bringing macroeconomic factors, including interest rates and exchange rates, down out of their upward movement to encourage investor confidence. Additionally, political stability plays a role in attracting FDI across various sectors. Hence, there must also be an effort to stabilize the political environment. Policymakers are urged to attach importance to these measures, thereby creating an environment conducive to investment in South Asian countries.